FAMILY SUPPORT AND INCREASING HYPERTENSION DIET BEHAVIOR AMONG ELDERLY - Urifah, Siti; Nasrudin, Nasrudin; Prihar Ninuk, Devin; Widodo, Heri (Nurse and Holistic Care, 2022)
Background: Hypertension is one of health problems that often occurs among elderly group. Complications caused by hypertension such as heart disease, kidney failure, diabetes mellitus, stroke and even death. The hypertension diet pattern is one of interventions to keep a normal blood pressure level, which also as a strategy to prevent related complications. Objective: The purpose of this study was to determine the correlation between family support and increasing hypertension diet behavior among the elderly in the village of Ngimbang, Tuban, East Java. Methods: The research design used a correlational analytic design with a cross sectional approach. This study was conducted at June 2022 in Ngimbang Village, Tuban-East Java, Indonesia. The population of this study was 23 elderlies in Ngimbang village who had hypertension, the sampling technique used total sampling and obtained a sample of 23 people. Data collection of both dependent data (family support) and independent data (diet behavior) used questionnaires and it was adopted from Utari (2017). Data analysis used Chi Square statistical test with (ρ < α = 0.05). Result: The result of this study showed that most of the elderly aged 60-70 years and the majority were women. The degree of hypertension was majority at 1st and 2nd. Moreover, half of the respondents have good family support and 78.3% of them were in good hypertension diet behavior. The results of statistical analysis tests showed that there was a relationship between family support and dietary behavior in elderly people with hypertension with ρ-value = 0.014 (ρ < α = 0.05). Conclusion: Collaboration between health workers and community leaders or cadres should be needed to provide counseling to the elderly and the families about good eating habits in the elderly who suffer from hypertension, so that with good eating habits it is hoped that blood pressure can be controlled and reduce the risk of complications.